MICROEARTHQUAKE HYPOCENTER ANALYSIS OF PATUHA GEOTHERMAL FIELD - Juliani Monica, Laurent
The Patuha Geothermal Field is located at West Java and is one of the geothermal fields that has produced 55 MW of energy. Energy production activities in geothermal fields will cause micro earthquakes. This micro earthquake event can be used to observe seismicity and subsurface conditions of the Patuha Geothermal Field, one of the methods is by analyzing the location of the micro earthquake hypocenter. 290 micro earthquakes were identified from the records of micro earthquakes carried out from 8 October 2019 to 10 December 2019. The initial hypocenter of the micro earthquakes was determined using the NonLinLoc method, and 279 micro earthquakes that had a hypocenter and an uncertainty value less than 0.2 was obtained. The VP/VS ratio value obtained from the Wadati plot diagram shows the number 1.6899, which indicates the presence of steam under the surface of the geothermal field. The relocation of the earthquake hypocenter using the Double-Difference method resulted in 236 earthquakes that could be relocated and had an uncertainty value less than 0.1. The initial hypocenter depth and the results of hypocenter relocation accumulated at an elevation of 0 - 1000 m, indicating that the earthquake occurred in the reservoir area, at the ends of the production wells, and thus the resulting earthquake was an earthquake caused by human activity. The results of the hypocenter relocation show that the accumulated earthquakes form a lineament can be interpreted as a fault zone.